The indicators of the physical health of students on the characteristics of the physical fitness, aerobic and anaerobic productivity of their body - T. B. Serorez (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : identification and assessment of physical health of students on physical performance characteristics, aerobic and anaerobic performance of their body. The objective of this study was to investigate the influence of cross-country training aerobic and anaerobic focus on physical performance, aerobic and anaerobic organism performance of students. Material : The study involved 413 students (boys ) aged 21 - 23 years. Efficiency of impact studies using cross-country loads of aerobic and anaerobic focus on the physical health of students. Results : It was found that the level of physical health of students on a scale of G.L. Apanasenko steadily deteriorating. Decrease is observed to a safe level in 22 years and further still below the safe level for 23 years. Anaerobic performance level of students in the body 21, 22 and 23 do not differ significantly and is below the average. Conclusions: confirmed that aerobic and anaerobic capacity of the organism students do not meet the proper level and require correction. Found that such a correction would be the most effective subject to the development and implementation of health technologies. Technology based on the use of extracurricular activities running exercises.